Native Warm-Season Grasses Show Limited Response to Phosphorus and Potassium - Eric Bisangwa; Jonathan D. Richwine; Patrick D. Keyser; Amanda J. Ashworth; David M. Butler; Utsala Shrestha; Forbes R. Walker (Agronomy)
Data are needed to identify optimum response to potassium (K) and phosphorus (P) amendment and associated mycorrhizal colonization for native warm-season grasses (NWSGs; big bluestem [BB; Andropogon gerardii Vitman] and switchgrass [SG; Panicum virgatum L.]). To evaluate these responses, experiments were conducted in Knoxville and Springfield, Tennessee, from 2013 to 2019. In twice-annual harvests, we assessed BB and SG dry matter (DM) yield, crude protein (CP), total digestible nutrients (TDNs), P and K removed by grasses (removal), and soil test P and K in response to P (29 to 88 kg ha−1) and K (70 to 257 kg ha−1) elemental rates, and rates of root colonization by mycorrhizal fungi in response to P. Amendments had no effect (p > 0.05) on DM yield, CP, or TDN for either species. Yield, CP, and TDN fluctuated among years (p < 0.001) for both species, but no consistent temporal trends were observed. Although removal exceeded inputs at the control (no input) for P and K, and at 70 kg K ha−1, there was not an associated reduction in soil test K and P values. Phosphorus rate affected (p = 0.02) total mycorrhizal colonization, with an average of 62% colonization across both species and 70% at the highest P rates. Given the lack of response for yield, CP, TDN, or associated soil nutrient test levels, NWSGs appear to offer a low-input option for forage production.